Pelaksanaan Pendidikan Agama Islam Anak Dalam Keluarga Melalui Metode Islamic Parenting - Binti Masrufa; Binti Kholishoh; Madkan Madkan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The study aims to study the role of the family in the implementation of Islamic education for children through Islamic Parenting methods in Langenharjo Village, Plemahan Kediri. The Islamic Parenting Method is an approach that focuses on Islamic values in educating children. Research is carried out using qualitative approaches, and data is collected through interviews, observations, and documentation studies. The results show that families play a central role in shaping children's character and religious understanding. Parents or guardians have a responsibility to give their children an understanding of religious teachings, morality, ethics, and Islamic examples. Islamic Parenting is an effective means for parents to teach basic concepts such as faith in Allah Subhanahu wa Ta'ala and Muhammad SAW as His Messenger, prayer (prayer), Ramadan fasting (fasting), zakat (infak), Hajj (sacrifice), and noble morality. The family is also the first place for children to learn the Quran and Hadith. Parents can read Islamic stories, teach values of goodness, and give positive examples in everyday life. Nevertheless, further efforts are needed to improve the understanding and implementation of Islamic Parenting methods in Langenharjo Plemahan Kediri Village. In conclusion, the role of the family is very important in the Islamic education of children. Islamic Parenting methods can be an effective means for parents to shape their children's Islamic character and strengthen their religious understanding. However, further efforts are needed to develop and disseminate these methods in society.